Traumatic pancreatic transection - Case reports (Journal of Kathmandu Medical College, 2020)
Pancreatic injury following blunt trauma abdomen is presentation with significant morbidity and mortality. Our first case here is the American Association for the Surgery of Trauma Organ Injury Scale (AAST-OIS) Grade V pancreaticoduodenal injuries following penetrating injury managed with pancreaticoduodenectomy and the second case is blunt trauma to the abdomen with pancreatic tail transection which is American Association for the Surgery of Trauma Organ Injury Scale (AAST-OIS) Grade III that was managed with Endoscopic Retrograde Cholangiopancreaticography (ERCP) and pancreatic duct stenting. The outcome depends on early diagnosis and needs a high index of suspicion due to subtle clinical and radiological findings initially. Hemodynamically unstable patients may have other associated visceral and vascular injuries, and damage control strategy will be a suitable option. Same sitting resection procedures like pancreaticoduodenectomy are rarely performed. Pancreatic injuries can often be managed non-operatively with percutaneous drainage and pancreatic duct stenting.